International space station spacecraft charging hazards: Hazard identification, management, and control methodologies, with possible applications to human spaceflight beyond LEO. Issue 4 (December 2020) - Koontz, Steve; Castillo, Terri; Hartman, William; Schmidl, William; Haught, Megan; Duncan, Gary; Gingras, Benjamin; Vera, Jerry
Abstract: In this paper, we present an overview of how the International Space Station (ISS) safety engineering methodology directed to controlling extravehicular activity (EVA) crew electrical shock hazards, caused by ISS spacecraft charging, has evolved over the past 25+ years. Long-term measurements of ISS charging severity and frequency-of-occurrence, combined with detailed probabilistic analysis of EVA electric shock-circuit completion, led to a change in hazard control methodology. The requirement for two-fault tolerant EVA shock hazard control during all EVAs was replaced with a less operationally burdensome and risky EVA shock hazard detection and warning process. The applicability of event probability-based detection-and-warning processes to human spaceflight charging hazard control beyond low-earth orbit (LEO) is also considered.